Planting the Seeds: The Impact of Training on Mango Producers in Haiti - Irani Arráiz; Carla Calero; Songqing Jin; Alexandra Peralta (Inter-American Development Bank (IDB), 2015)
This paper evaluates the short-term impacts of a development project that aims to increase mango yields, sales of mango products, and the income of small mango farmers in rural Haiti. Various matching methods, in combination with difference-in-difference (DID), are used to deal with the potential selection bias associated with nonrandom treatment assignment. Robustness checks are conducted to investigate whether and to what extent the results are affected by the coexistence of other similar projects in the same sites. Rosenbaum bounds analysis is carried out to check the sensitivity of the estimated impacts—based on matching methods—to deviations from the conditional independence assumptions; the relative importance of unobserved factors in the decision to participate. Our results show that in a 16-month period, the project increased the number of young Francique trees planted—a type that has greater market and export potential than traditional mango varieties—and likely encouraged the adoption of best practices. But the project has not yet led to a noticeable increase in total sales. The adoption of improved production practices is too recent to translate into significant changes in production and sales. While the robustness check suggests that the results are not caused by the presence of other similar programs on the same sites, the Rosenbaum bounds sensitivity analysis suggests that the matching results are robust against potential "hidden bias" arising from unobserved outcome variables in some but not all cases.
hdl:11319/7184
Keywords: C23; E2; F36; 330